Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Asli Daerah Di Kabupaten Klaten Tahun 1990-2012 - Yunanto, Rusera Ricko (2016)
This study entitled "Analysis of Factors Affecting Local Revenue in Klaten Regency Year 1990-2012". The objective is to analyze the effect of regional gross domestic product, investment in population and government expenditure on revenue in Klaten district in 1990-2012. The dependent variable in the form of local revenue (PAD), while the independent variable in the form of regional gross domestic product (GDP), investment (I), population (JP) and government spending (G). This study uses secondary data (time series) with a multiple linear regression analysis method Partial Adjustment Model (PAM). To test the validity of the models tested include: normality test, linearity test, classic assumption test (test multicollinearity, heteroscedasticity test and autocorrelation test). Followed by statistical analysis include: t-test, F, R2 and interpretation. The results showed that: The result of the calculation of data normality test with normal distribution model of Jarque Bera; Linearity test results with the model of Ramsey Reset shaped linear regression model; The test results indicate that there is classical assumption multicolinearity problem, no problem heterokedastisitas, and there is no problem of autocorrelation; T test results showed that the variables that have a significant effect on revenue is variable in government spending (in the short term and long term) and local revenues the previous year (on short term), while the variables of the GDP, population, investment has no significant effect on short-term and long-term; F test results showed that the GDP variable, population, investment, government spending significant effect on local revenues.